Tindak Pidana Penipuan Dalam Dimensi Cyber Crime (Studi Kasus Polres Kota Palu) - Abdul Wahid (Universitas Merdeka Madiun, 2022)
The formulation of the problem in this study are: (1) How is the process of investigating online fraud crimes in the Palu Police area?. (2) What are the obstacles in the process of investigating online fraud in the Palu Police area?. The author's objectives in conducting this research are as follows: To find out the process of investigating online fraud in the Palu Police area. To find out the obstacles in investigating online fraud cases in the Palu Police area. To find answers to the formulation of the problem that has been formulated, the author uses empirical research methods, namely a study obtained directly from data sources and several documents and references related to fraud offenses. In order to conduct research related to the object to be studied, this research was conducted at the Criminal Investigation Unit of the Palu Police. This place was chosen as the research location on the basis of the community's main choice to carry out legal protection or make reports on criminal cases, especially criminal acts of fraud. The results and conclusions in this study are: the process of investigating online fraud crimes handled by the hammer resort police based on police reports, sending a notification letter for the start of the investigation, expert hands, blocking the suspect's account number, then coordinating with the local police station where the suspect is, then arresting the suspect, Detention, confiscation, collection of evidence, examination of suspects, After the case file is declared complete, it is submitted to the prosecutor's office. Obstacles in the Investigation Process Online fraud crimes are as follows: The perpetrator uses a false identity. Delete account and phone number. The perpetrator is outside the Central Sulawesi area. Tool limitations